2011
DOI: 10.4028/www.scientific.net/ssp.170.97
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Nanocrystalline (Fe,Co)<sub>3</sub>О<sub>4</sub>-Based Alloys and their Magnetic Properties

Abstract: The structure of nanocrystalline Fe-Co-O alloys produced by high-energy ball milling and subsequent low-temperature annealing were investigated by X-ray diffraction analysis, scanning and transmission electron microscopy. The magnetic properties were measured in vibrating sample magnetometers at room temperature. The mixtures of FeO and Co powders were used as starting materials. The nanocrystalline composite alloys, obtained as a result of the milling, contained FeO and -Fe with the crystallite size of 12-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…5). As an example, Figure 6 shows the dark-field image (taken in reflection of (FeCo) 3 O 4 phase) of FeO+20 % Co powder subjected to high-energy milling for 6 h and subsequent annealing at 250 о С for 8 h. It is seen that a particle 0.5-0.6 µm in size includes (Fe,Co) 3 O 4 nanocrystallites 10-30 nm in size It was found that the coercive force of Fe-Co-O alloys containing of about 80 vol % of the (FeCo)3O4 phase reaches µ 0 H ci ≈ 0.08 T [7].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…5). As an example, Figure 6 shows the dark-field image (taken in reflection of (FeCo) 3 O 4 phase) of FeO+20 % Co powder subjected to high-energy milling for 6 h and subsequent annealing at 250 о С for 8 h. It is seen that a particle 0.5-0.6 µm in size includes (Fe,Co) 3 O 4 nanocrystallites 10-30 nm in size It was found that the coercive force of Fe-Co-O alloys containing of about 80 vol % of the (FeCo)3O4 phase reaches µ 0 H ci ≈ 0.08 T [7].…”
Section: Resultsmentioning
confidence: 98%
“…Structure and properties of magnetite-based powders. Magnetic alloys based on the Fe 3 O 4 magnetite are of substantial interest [5][6][7]. It was shown that, in using the mechanochemical treatment of Fe 2 O 3 +Fe, Fe 2 O 3 +Fe+Co and FeO+Co mixtures and subsequent annealing of synthesized material, hardmagnetic powders can be prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation